CO-MANAGEMENT UNTUK MENGINISIASI PENYELESAIAN KONFLIK DI TAMAN NASIONAL LORE LINDU - Saharia Kassa; Hadi S. Alikodra; Bunasor Salim; Sambas Basuni (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research aims were to analyze stakeholder interests in affecting conflict at Lore Lindu National Park, and to analyze the key factor determining in the success of co-management as an approach in Lore Lindu National Park management. The village sample determination was conducted using a Stratified Random Sampling method, while 90 local community respondents were determined using a Systematic Random Sampling method, in which 45 people were taken from villages where the conservation community agreement (KKM Villages) has been established and the other 45 people from villages where there was no conservation community agreement (Non-KKM villages). There were 6 respondents from the Lore Lindu National Park Authority (BTNLL), 3 respondents from non- governmental organization (NGO), and 6 respondents were researcher/academicians determined using the Purposive Sampling method. The results of the study showed that the stakeholder interests affecting conflict at the Lore Lindu National Park were custom land uses within the Park area, boundary pole reconstruction, rattan extraction, illegal logging, and protected wildlife hunting. In addition, the key factors determining the co-management success were stakeholder involvement, negotiation, territory boundary, consensus, clarity of right and responsibility, local community right recognition, and applying the custom punishment.